The implementation of tolerance values through multicultural education program - Setiawan, Aziz; Purnomo, Panji; Marzuki, Marzuki; Charismana, Dian Satria; Zaman, Akhmad Roja Badrus (Universitas Negeri Yogyakarta, 2024)
This research aimed to delineate the strategies for fostering tolerance among students through multicultural education at Sanggar Anak Alam Nitiprayan in Yogyakarta. Employing a qualitative methodology with a case study approach, the investigation was conducted within the premises of Sanggar Anak Alam Nitiprayan located in Bantul, Yogyakarta. Data gathering methods encompassed interviews, observations, and documentation, with subjects selected purposively. Triangulation was utilised to ensure data validity. Analysis followed the qualitative data analysis technique advocated by Miles & Huberman, involving stages of data collection, reduction, presentation, and conclusion drawing. The study yielded two principal findings: firstly, the integration of tolerance values into the school curriculum through multicultural education, and secondly, the cultivation of tolerance within classrooms via daily encounters, class agreements, communal prayer, and storytelling activities. Identified obstacles included diverse student potentials, varying parental attitudes, parental indoctrination conflicting with the SALAM curriculum, student non-compliance with agreements, facilitators adopting a lecturing rather than a facilitating role, and difficulties transferring students from formal educational backgrounds faced in adapting to the new environment.